PENYULUHAN TENTANG MANFAAT DAUN SEDUHAN KOPI ROBUSTA DALAM MENURUNKAN TEKANAN DARAH PENYAKIT HIPERTENSI DI PUSKESMAS BIRU-BIRU - Linta Meliala (INSTITUT KESEHATAN DELI HUSADA, 2021)
Background :A diuretic is a drug that can increase the speed of urine volume. The diuretic term has two meanings, the first being indicating increased volume the urine produced and the second shows the amount of ingested substances ingested in water. The caffeine in coffee can cause a weak diuretic because it increases glomerular filtration and decreases inatrium reabsorbs in the renal tubules. Robusta coffee beans are coffee beans that are very easy to grow and easier to harvest, because these coffee beans are less sensitive to climate, so they will always be there to be harvested and this robusta coffee plant has a lot of fruit. This research is meant to find out robusta’s (Coffeacanephora) brew effect on the urine profile and urine volume of the rat white. Method : Samples were 20 male white rats as test animals and were divided into five groups of four in each The positive control group using furosemide 5,04 mg/kgbb, CMC Na 0,5 % is given as a negative control group and than group treatment of an brewing coffee with a dose of 600, 300, 150 mg/kgbb oral injection. Urine measurements were done on the hour to 1, 2, 3, 4, 5, and 6. Result :The study shows robusta coffee brewing with a dose of 600 mg/kgbb shows increased urine volume compared to the dose of 300, and 150 mg/kgbb. Conclusion :robusta coffee seduces have a diuretic effect on male white rat no better than furosemide.